Efektifitas Aplikasi E-Kinerja dalam Meningkatakan Profesionalisme Guru - Aulia, De Syifa Adha; Iswanto, Tedi; Ramdani, Deni; Asmara, Anjas (Bildung: Jurnal Ilmu Pendidikan, 2026)
This study aims to analyze the effectiveness of the e-Performance (e-Kinerja) application in enhancing teacher professionalism at SMP Negeri 3 Karangnunggal. A qualitative approach with a case study design was employed. Data were collected through interviews with the school principal, observations, and document analysis related to the implementation of the e-Performance system. The findings indicate that the effectiveness of e-Performance implementation is influenced by technological infrastructure readiness, particularly internet network stability, as well as teachers’ digital literacy competencies. The use of e-Performance encourages improved work discipline, professional responsibility, and compliance with performance reporting based on measurable indicators. Furthermore, e-Performance contributes to the development of a performance-based work culture through an objective and accountable performance appraisal system. The documented performance data are also utilized as a basis for performance evaluation and career development of civil servant and contract-based teachers. Therefore, e-Performance plays a strategic role in supporting the sustainable enhancement of teacher professionalism.